2017
DOI: 10.18006/2017.5(2).271.276
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apa I polymorphism of vitamin d receptor gene with type 2 diabetes mellitus in Saudi population

Abstract: KEYWORDS VDR ApaI ABSTRACTVitamin D deficiency has been associated with the acceleration of the onset of T2DM. The biological effects of vitamin D are mediated by binding to the vitamin D receptor (VDR) which belongs to the steroid receptor superfamily. Although many polymorphisms exist in the VDR gene, their effect on VDR protein function and signalling is unknown. An association between VDR polymorphism and T2DM has been reported in some studies; however, it appears to vary across different populations aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…DM is a group of metabolic disorders which is characterized by a chronic hyperglycemic condition resulting from defects in insulin secretion, insulin action or both. Although many studies have been carried out on the VDR gene and its association with various types of diabetes, the results seem to be highly population dependent (Iyer et al, 2017). Our study has clearly shown that the recessive t allele at TaqI site is associated with the prognosis of GDM.…”
Section: Discussionmentioning
confidence: 61%
“…DM is a group of metabolic disorders which is characterized by a chronic hyperglycemic condition resulting from defects in insulin secretion, insulin action or both. Although many studies have been carried out on the VDR gene and its association with various types of diabetes, the results seem to be highly population dependent (Iyer et al, 2017). Our study has clearly shown that the recessive t allele at TaqI site is associated with the prognosis of GDM.…”
Section: Discussionmentioning
confidence: 61%
“…Our results are consistent with those reported in other studies in several countries indicating that there is no significant association of this SNP with type I diabetes (Denise et al, 2009, Lemos et al, 2008). A recent study showed that the FokI polymorphism is a risk factor for insulin resistance and susceptibility to type 2 diabetes (Iyer et al, 2017). Several groups have reported that VDR - FokI polymorphism is associated with cancers and autoimmune diseases, although the mechanisms remain to be determined (Dankers et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies on the T2DM population in Jeddah, Saudi Arabia, showed the genotype and allele of the Apa-I Vitamin D receptor gene polymorphism as a risk factor for developing T2DM [8], but on the T2DM population in Turkey and Mexico showed the different results [9], [10]. Based on differences in the previous studies in various populations, this present study aims to analyze the role of the Apa-I Vitamin D receptor gene polymorphism in T2DM patients in the Universitas Sumatera Utara Hospital.…”
Section: Introductionmentioning
confidence: 99%